Earthquake Occurrences of the Major Tectonic Terranes for the Arabian Shield and Their Seismic Hazard Implications - Ali, Sherif M.; Abdelrahman, Kamal (Frontiers in Earth Science, 2022)
The Arabian Shield, which contains a group of diverse terranes accreted during the Late Proterozoic, has experienced considerable historical and recent earthquake activities. From north to south, the Midyan terrane, Tabuk-Neom area, Hijaz terrane, Jeddah terrane, and Asir terrane make up the western section of the Arabian shield. In order to determine the earthquake occurrences and earthquake recurrence characteristics in the study area, an earthquake dataset containing 2991 seismic events recorded between 1941-2019 with magnitudes 1.0 and 6.2 and depths between 0-50 km was examined. The data was compiled by combining phase readings, origin times, hypocenters parameters and magnitudes reported by the International Seismological Centre. The maximum likelihood method has been applied to calculate the Gutenberg–Richter recurrence parameters (a- and b-values) and magnitudes of completeness (Mc). The range of b-values is 0.53-1.04, which indicates that the study region experienced different stress level accumulations that cause earthquakes with different magnitudes. The Hijaz terrane is characterized by a high b-value (1.04±0.34), which indicates a relatively low stress regime that was resulted from the earthquakes stress release. The Midyan terrane is characterized by a low b-value (0.53±0.10), which could be indicative of a relatively higher stress regime associated with a dominantly extensional stress. Mc values were found to be 1.4 in Midyan and Jeddah terranes. The lower value of Mc at Midyan terrane demonstrates appropriate stations distribution and high earthquake rates. However, at Jeddah terrane the seismic activities are poorly detected that probably lead to the small value of Mc. Higher Mc are evident in Hijaz terrane (Mc=2.3) and Tabuk-Neom (Mc=2.4), where the stations distribution is very poor. The maximum expected magnitudes (Mmax) are found to be 6.0 for Midyan terrane, 5.4 for Tabuk-Neom, 4.7 for Hijaz terrane, 4.8 for Jeddah terrane and 7.7 for Asir terrane. The average recurrence intervals of earthquakes with the Mmax are ~7, ~20, ~6, ~120 and ~200 years for each seismic terrain, respectively. The probability of occurrence and returned periods of different magnitudes in each region indicate that regions related to the Najd strike-slip fault system are the regions for large probable earthquake occurrences.